Novel synthesis of nickel-iron hexacyanoferrate nanoparticles and its application in electrochemical sensing - Pandey P.C.; Panday D. (My University, 2025)
We report herein a novel method for the synthesis of nickel-iron hexacyanoferrate nanoparticles involving the participation of tetrahydrofuran and hydrogen peroxide. It has been found that desired ratio of potassium ferricyanide and nickel sulphate is converted into nickel-iron hexacyanoferrate nanoparticles in the presence of tetrahydrofuran and hydrogen peroxide within 30 min at 60 °C. The as synthesized nickel-iron hexacyanoferrate nanoparticles have been characterized by UV-Vis spectroscopy, Fourier transformation infrared spectroscopy (FT-IR), X-ray diffraction analysis (XRD), energy dispersive spectroscopy analysis (EDS), Transmission Electron Microscopy (TEM) and cyclic voltammetry. The average sizes of nanoparticles are found in the order of 31 nm. The nickel-iron molar ratio significantly influences the electrochemical behaviour of as synthesized nanoparticles modified electrode. Electrochemical sensing of hydrazine has been examined on mixed metal hexacyanoferrate modified electrode with analytical sensitivity in the order of 135.76 μA mM- 1 cm- 2 and lowest detection limit of 50 nM. Apart from its use in electrochemical sensing, mix metal nanoparticles are soluble in aqueous media and show excellent peroxidase mimetic activity with the Michaelis-Menten constant and Vmax in the order of 1.5 mM and 3.06 × 10- 7 m s- 1 respectively for H2O2 mediated oxidation of o-dianisidine thus representing novel material for both homogeneous and heterogeneous catalysis. © 2015 Elsevier B.V. All rights reserved.